2006
DOI: 10.1007/s11274-006-9211-8
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of an alkaline protease of Aspergillus clavatus

Abstract: An extracellular alkaline serine protease has been purified from a strain of Aspergillus clavatus, to apparent homogeneity, by ammonium sulfate precipitation and chromatography on Sephadex G-75. Its molar mass, estimated by SDS-PAGE, was 35 kDa. Maximum protease activity was observed at pH 9.5 and 40°C. The enzyme was active between pH 6.0 and 11.0 and was found to be unstable up to 50°C. Calcium at 5 mM increased its thermal stability. The protease was strongly inhibited by PMSF and chymostatin as well as by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 13 publications
(10 reference statements)
5
23
2
Order By: Relevance
“…The thermal stability profile of the enzyme showed an initial retention of 96% activity after 1 h of incubation at 40 °C , whereas, 84 and 53 % of residual activities were scored at 45 and 55 °C , respectively. It also showed that protease from A. flavus was relatively thermostable when compared to other reports for the same organism (Tremacoldi et al 2007, Tunga et al, 2003.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The thermal stability profile of the enzyme showed an initial retention of 96% activity after 1 h of incubation at 40 °C , whereas, 84 and 53 % of residual activities were scored at 45 and 55 °C , respectively. It also showed that protease from A. flavus was relatively thermostable when compared to other reports for the same organism (Tremacoldi et al 2007, Tunga et al, 2003.…”
Section: Discussionsupporting
confidence: 50%
“…However, an increase in temperature beyond 55 °C resulted in the inactivation of enzyme. Wang et al (2005) and Tremacoldi et al (2007) also reported alkaline protease from Aspergillus sp. having optimum activity at 40 °C .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…1b). The different molecular weight of the alkaline proteases were obtained from other Aspergillus species such as 124 kDa serine protease from A. fumigatus [32], 33 kDa from A. fumigatus [33], 35 kDa from A. clavatus [6], 37 kDa from A. terreus [16], 23 kDa from A. parasiticus [17]. Based on our knowledge, Ansari and Stevens [34] have only isolated two neutral proteases and characterized from A. nidulans and their molecular weights were 30.9 kDa and 30 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…Protein bands that look thin, it is interpreted that the concentration of the enzyme dilution buffers is too high, with 10 times dilution (enzyme 1: buffer 9). Tremacoldi et al, (2007) [20] reported that a mixture of enzyme and buffer from the results of his research is 10:50 or (1:5). Asker et al, (2013) [6] also undergo dialysis to enzyme alkaline protease from Bacillus megatherium with a ratio of enzymes and buffers are (1:2), so that the better comparison between the buffer and the enzyme protein concentrations were stuck in the pockets of dialysis is higher.…”
Section: Characterization Of the Molecular Weight Of The Alkaline Promentioning
confidence: 99%